Keberagaman Agama dan Urgensi Toleransi - Nuraeni, Heni Ani; Putri, Dessy Marsellya; Akasyah, Syira Aulia (Jurnal Ilmiah Wahana Pendidikan, 2024)
The rich tapestry of Indonesia encompasses diverse ethnicities, civilizations, races, and faiths. This diversity, present in all religions, can sometimes lead to clashes among religious groups. Recognizing this, there is a growing awareness of the necessity for society to embrace a more tolerant mindset. Islam, with its principles of tolerance, plays a significant role in this context. Islam upholds the right of every individual to freely practice any religion of their choice. In promoting unity and peace within the realm of religious life, Islam is frequently acknowledged as a trailblazer in fostering tolerance. The objective of this paper is to offer a theoretical exposition of the Islamic perspective on tolerance among different faiths. The expectation is that this study will add to the existing body of knowledge. Employing a systematic approach, this research relies on methodical library research. The outcomes of this study revolve around the foundational aspects of religious tolerance within Islam, the principles guiding religious tolerance, and the limits of tolerance within religious communities